ІДЕАЛ УЧИТЕЛЯ: ПОРІВНЯННЯ ІДЕЙ ЯКОВА ЧЕПІГИ ТА ПЕДАГОГІВ КІНЦЯ ХІХ – ПОЧАТКУ ХХ СТ. - Bogdanets-Biloskalenko, N (Continuing Professional Education: Theory and Practice, 2019)
In the article appearance of teacher is analysed in the looks of teachers of end of ХІХ – to beginning of ХХ age. In detail rozglyatuto labours are studied opinions of Jacob Plough-tails in relation to a teacher, which an ideal teacher must be to. Importance of role of teacher is determined in society and a method, offered Ya.Chepigoy, is outlined, which provides obvious authority, exemplaryness and irreproachability of moral qualities of teacher. Also in the article it is laconically refl ected and the ideas of teachers are compared – contemporaries of Ya.Chepigi. In particular B.Grinchenko, S.Rusovoy, K.Ushinskogo, T.Lubencya, O.Dukhnovicha. Analysing the scientifi c inheritance of Ya. Chepigi in comparing and comparison to his colleagues, exactly in the aspect of ideal of teacher, make sure, that each of them in realization of far-sighted nationally elucidative plans of studies and education at school considered a teacher a central fi gure.